Handling Of Minor Crime Cases (Tipiring) Through Restorative Justice As An Effort To Overcome Overcapacity Of Prisoners - Yudi Setiawan, Dwi (CV. Inara, 2022)
As one of the sub-systems of criminal justice, correctional institutions (Lapas) have a role in the implementation of fostering prisoners and correctional students through a correctional system based on education, rehabilitation, and reintegration. In Law Number 12 of 1995 concerning Corrections, it is stated that the correctional system is held in order to form correctional inmates so that they become fully human, realize mistakes, improve themselves, and do not repeat criminal acts so that they can be accepted again by the community. However, in its development, the guidance carried out is not optimal due to the complexity of the problems that occur in prisons. One of the root causes of problems in prisons/detention centers is overcapacity. Various policies have been taken to overcome the overcapacity problem, including through building rehabilitation to the construction of new buildings with the aim of increasing the capacity of prisons and detention centers. However, this policy was not significantly able to overcome the problem of overcapacity considering the increasing number of detainees and inmates who are still much more as a result of the high level of crime in the community. Efforts that may be more appropriate to do to overcome the excess capacity in prisons can be taken by using a Restorative Justice approach, namely a shift in punishment in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punishments such as social work. and others. this policy was not significantly able to overcome the problem of overcapacity considering the increasing number of detainees and inmates who are still much more as a result of the high level of crime in the community. Efforts that may be more appropriate to do to overcome the excess capacity in prisons can be taken by using a Restorative Justice approach, namely a shift in punishment in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punishments such as social work. and others. this policy was not significantly able to overcome the problem of overcapacity considering the increasing number of detainees and inmates who are still much more as a result of the high level of crime in the community. Efforts that may be more appropriate to do to overcome the excess capacity in prisons can be taken by using a Restorative Justice approach, namely a shift in punishment in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punishments such as social work. and others. Efforts that may be more appropriate to do to overcome the excess capacity in prisons can be taken by using a Restorative Justice approach, namely a shift in punishment in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punishments such as social work. and others. Efforts that may be more appropriate to do to overcome the excess capacity in prisons can be taken by using a Restorative Justice approach, namely a shift in punishment in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts in addition to alternative punishments such as social work. and others.